Validation of CALINE4 modelling for carbon monoxide concentrations under free-flowing and congested traffic conditions in Ireland. (18th July 2005) - Broderick, B.M.; Budd, U.; Misstear, B.D.; Ceburnis, D.; , S.G. Jennings
Atmospheric dispersion model accuracy is dependent not only on the quality of the data used, but also on the methodology of the model and its user. The air pollution dispersion model CALINE4 (Benson, 1984; 1992) is commonly used in Ireland but was developed outside Ireland and has not been validated for use in Irish conditions. The objective of this work was to validate the use of the model for road traffic emissions in Ireland. However, the results will also be of wider European interest. The model was assessed using one year of air quality data collected at two sites: a free-flowing motorway and a periodically congested roundabout. Model predictions of CO concentrations were generally within ±50% of measured concentrations, though under stable atmospheric conditions, and when wind speeds are low, significant discrepancies may arise. The major difficulty in modelling was found to be the scarcity of local traffic, meteorological and background concentration data.